Extremal zagreb indices of unicyclic graphs - Chen, Shubo; Zhou, Houqing (Utilitas Mathematica, 2019)
The Zagreb indices are topological indices of graphs, which defined as, M(G) = £ = £ t>eV(G) uvE(G) this paper, we determine the upper and lower bounds for the Zagreb indices of unicyclic graphs in terms of their order and girth. In each case, we characterize the extremal graphs. © 2019 Utilitas Mathematica Publishing Inc.. All rights reserved.